The Status of Criminal Law in the Order of Implementation of Duties and Authorities of Authorized Land Marker - Dewa Gede Wibhi Girinatha (Warmadewa Press, 2020)
The problem discussed in this study is the authority of the land deed maker in making authentic deeds and potential criminal offenses in carrying out the position of the official land deed maker, because it is very important for the officials of the land deed maker in assuming his position to provide services and information about agreements to make land certificates and for the public interest. This study aims to examine the position of criminal law in the order of carrying out the duties and authorities of the official land deed. This study was designed in juridical-empirical research. The result of this research is that the official land deed maker is inseparable from the responsibility of the deed he made and the implementation of the position of Land deed official has the potential to cause a criminal offense. Potential criminal offenses referred to are potential criminal offenses in the implementation of Land Titles Registrar positions in falsifying authentic deeds regulated and threatened with criminal offenses in Article 264 paragraph (1) jo. Article 263 of the Criminal Code. The falsification of the letter is punishable by imprisonment for a maximum of eight years, if it is carried out on authentic deeds in Article 264 paragraph (1) number 1 of the Criminal Code.